MELAMPAUI KONVENSIONAL: EFEKTIVITAS PEMBELAJARAN BERDIFERENSIASI DALAM MENGEREK MINAT BELAJAR GEOGRAFI SISWA FASE E - Nurfalah; Ade Irma Suryani; Trina Febriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the problem encountered in teaching and learning activities (KBM) where most students are less enthusiastic in following the ongoing geography teaching and learning process, especially if the teacher only uses conventional methods such as lectures when delivering a material and discussing in groups. This study aims to determine the effectiveness of implementing differentiated learning methods to increase students' interest in learning geography subjects phase e at SMA Negeri 1 Lembah Melintang. The study adopted a quasi-experimental design. The population in this study were all phase E students at SMA Negeri 1 Lembah Melintang registered in the 2024/2025 academic year consisting of 10 phases with a total of 360 students. The sampling technique used in this study was random sampling carried out in phase E 9 and phase E 10. Data were collected using tests, questionnaires and documentation and analyzed through the T test. The findings revealed that the application of differentiated learning methods to increase students' interest in learning geography subjects phase E at SMA Negeri 1 Lembah. This study concludes that there is a difference in increasing student learning interest using differentiated learning in phase E at SMA Negeri 1 Lembah Melintang. Based on the average percentage score obtained from the learning interest variable, students in the experimental class scored higher than the average percentage score in the control class, thus categorizing the respondents' achievement as good.